PERAN PENDIDIKAN MULTIKULTURAL DALAM PEMBELAJARAN IPS UNTUK MEMBENTUK KARAKTER TOLERANSI PADA ANAK KELAS V SDN CIPINANG CEMPEDAK 01 PAGI - Indah Oktaviana, Nur; Angger Wardhani, Prayuningtyas; Wardatussa’idah, Indah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Intolerance towards multiculturalism in elementary schools is still a major challenge in the world of education today. Therefore, the aim of this research is to evaluate the extent to which multicultural education plays a role in Social Sciences (IPS) learning in forming students' tolerant character. The research method used is descriptive qualitative, where data is obtained through observation, interviews and document analysis. The research results show that multicultural education in social studies learning has a very important role in forming students' tolerant character. These findings confirm that multicultural education in social studies learning significantly influences the formation of students' tolerant character.